Nanomaterials targeting cancer stem cells to overcome drug resistance and tumor recurrence - Kumbhakar, Divya Vishambhar; Thakkar, Lucky; Akhand, Chetana; Sharaf, Shehna; Vemuganti, Geeta K. (Frontiers in Oncology, 2025)
A cancer stem cell (CSC) is an immortal cell that is capable of self-renewal, continuous proliferation, differentiation into various cancer cell lineages, metastatic dissemination, tumorigenesis, maintaining tumor heterogeneity, and resistance to conventional treatments. Targeted therapies have made huge advances in the past few years, but resistance is still a major roadblock to their success, in addition to their life-threatening side effects. Progressive treatments are now available, including immunotherapies, CRISPR-Cas 9, sonodynamic therapy, chemodynamic therapy, antibody–drug nanoconjugates, cell-based therapies, gene therapy, and ferroptosis-based therapy, which have replaced surgery, chemotherapy, and radiotherapy for cancer treatment. The challenge is to develop targeted treatment strategies that are effective in eradicating CSCs, as they are resistant to anticancer drugs, causing treatment failure, relapse, and recurrence of cancer. An overview of the fundamental characteristics of CSCs, drug resistance, tumor recurrence, and signaling pathways as well as biomarkers associated with their metastatic potential of CSC is elucidated in this review. The regulatory frameworks for manufacturing and conducting clinical trials on cancer therapy are explicated. Furthermore, we summarize a variety of promising nanocarriers (NCs) that have been used directly and/or synergistic therapies coupled with the therapeutic drug of choice for the detection, targeting, and imaging of CSCs to surmount therapeutic resistance and stemness-related signaling pathways and eradicate CSCs, hence alleviating the limitation of conventional therapies. Nanoparticle-mediated ablation therapies (NMATs) are also being argued as a method for burning or freezing cancer cells without undergoing open surgery. Additionally, we discuss the recent clinical trials testing exosomes, CRISPR/Cas9, and nanodrugs, which have already received approval for several new technologies, while others are still in the early stages of testing. The objective of this review is to elucidate the advantages of nanocarriers in conquering cancer drug resistance and to discuss the most recent developments in this field.